COVID-19 in pediatric patients undergoing chronic dialysis and kidney transplantation - Canpolat, Nur; Yildirim, Zeynep Yuruk; Yildiz, Nurdan; Tasdemir, Mehmet; Goknar, Nilufer; Evrengul, Havva; Gulmez, Ruveyda; Aksu, Bagdagul; Dursun, Hasan; Ozcelik, Gul; Yavascan, Onder; Cicek, Rumeysa Yasemin; et al. (SPRINGER, 2022)
The study aims to present the incidence of COVID-19 in pediatric patients undergoing renal replacement therapy (RRT) and to compare the severity and outcomes of the disease between the dialysis and kidney transplant (KTx) groups. This multicenter observational study was conducted between 1 April and 31 December 2020 in Istanbul. Members of the Istanbul branch of the Turkish Pediatric Nephrology Association were asked to report all confirmed cases of COVID-19 who were on RRT, as well as the number of prevalent RRT patients under the age of 20. A total of 46 confirmed cases of COVID-19 were reported from 12 centers, of which 17 were dialysis patients, and 29 were KTx recipients. Thus, the incidence rate of COVID-19 was 9.3\% among dialysis patients and 9.2\% among KTx recipients over a 9-month period in Istanbul. Twelve KTx recipients and three dialysis patients were asymptomatic (p = 0.12). Most of the symptomatic patients in both the dialysis and KTx groups had a mild respiratory illness. Only two patients, one in each group, experienced a severe disease course, and only one hemodialysis patient had a critical illness that required mechanical ventilation. In the entire cohort, one hemodialysis patient with multiple comorbidities died. Conclusion: While most cases are asymptomatic or have a mild disease course, pediatric patients undergoing dialysis and a kidney transplant are at increased risk for COVID-19. What is Known: In adult population, both dialysis patients and kidney transplant recipients are at increased risk for severe illness of COVID-19 and have higher mortality rate. Children with kidney transplantation are not at increased risk for COVID-19 and most have mild disease course. Data on children on dialysis are scarce. What is New: Pediatric patients undergoing dialysis and kidney transplantation have an increased risk for COVID-19. Most patients undergoing renal replacement therapy either on dialysis or transplanted develop asymptomatic or mild COVID-19 disease with a favorable outcome.
Keywords: Children; COVID-19; Dialysis; Kidney transplantation; Pediatric; Renal replacement therapy; RRT